Application of the Internet of Things in Controlling the Water Content Quality of Honey - Purba, Arini Anestesia; Isabella, Mayati; Kumalaningrum, Amalia Nur; Aqilasyam, Rafa Ahza; Alfian, Ricky; Imran, Ali; Zanuar F, Naufal; Adi F, M. Akbar; Sianipar, Rimma (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Agriculture is one of the key aspects of a nation’s survival. In support of the Astacita Program of the President and Vice President of the Republic of Indonesia, which aims for food self-sufficiency, this research focuses on the topic of food security. In practice, food security faces several challenges, such as production that does not meet quality standards and very low productivity levels. One example is the cultivation of Kalimantan honey bees. Honey is one of Kalimantan’s natural resources that is highly beneficial for enhancing the human immune system. According to the Indonesian National Standard (SNI) 8664:2018, the acceptable water content in honey should be less than 22%. However, in reality, the water content in honey often exceeds 22%, reaching up to 27%. The purpose of this research is to reduce the water content in honey so that its shelf life can be extended to six months, making it suitable for export. This study employs an Internet of Things (IoT) approach, involving the stages of planning, analysis, design, implementation, testing, and evaluation. The research produced a device capable of reducing the water content of Trigona honey (27%) to meet SNI standards within 5 hours, Cerana honey (43%) within 7 hours, and Dorsata honey (30%) within 9 hours. The use of this device proved effective in lowering honey’s water content to below 22%, in compliance with SNI standards, which means the honey becomes more durable, marketable, and exportable. This research is expected to contribute to strengthening food security in the city of Balikpapan.